FIRST RECORD OF Balanophora elongata var. ungeriana SPECIES IN SOUTH SUMATRA - Pragustiandi, Guntur; Sarno, Sarno; Windusari, Yuanita; Pirnanda, Dafid; Setiawan, Doni (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2020)
The study of Balanophora in South Sumatra has been carried out from July-August 2018. This research uses the direct observation and collection method in 3 km long track in the Bukit Jambul Gunung Patah Protection Forest Area, South Sumatra. Sample identification was carried out in the Biology Department of the Faculty of Mathematics and Natural Sciences, Sriwijaya University. The results show that there is one Balanophora species, B. elongata. There are 2 subspecies of this species, namely B. elongata var. elongata and B. elongata var. ungeriana (Valeton) B. Hansen. The difference between these 2 subspecies is var. ungeriana in the tubers is not elongated with longitudinally coarse luruk leaves. At that location only found species of B. elongata var. ungeriana. Distribution: Peninsula Malaysia, Borneo, Sumatra, Java, and mostly in West Java for subsp. ungeriana is only recorded on the island of Java precisely at Mount Salak and Mount Gede in West Java. This species is the first record for the Sumatra Island. There are around 30 individual species of B. elongata var. ungeriana respectively 23 female individuals and 7 male individuals. Bulbs, leaf characters and flower types are important to identifying the species of Balanophora. Most of these species are found in habitats where they have a height of 1000-2800 meters above sea level which are suitable for habitat in the Bukit Jambul Gunung Patah Protection Forest Area.